Persuasive techniques of life insurance agents: an analysis of sales strategies and customer perceptions in the Philippines - Barrio, Rose Vhirneil; Baculanlan, Mary Margareth; Ecleo, Kyla Shaine; Gonjoran, Marifel Ralyn; Sabido, Emmanuel; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
In today's fast-paced market, skilled life insurance agents artfully employ diverse techniques to captivate customers, customizing their approach to satisfy unique needs and confidently promote life insurance policies. This study delves into the fascinating world of sales strategies employed by life insurance agents and takes a closer look into the underlying factors that influence customer perceptions. Using a qualitative survey of 10 life insurance agents and 10 customers in Tacloban City, the study investigates the persuasive techniques used by life insurance agents to sell policies, and the perceptions of customers about these techniques. Through the conduct of a thorough semi-structured interview and through the application of rigorous thematic analysis, the responses of the participants revealed eleven commonly used persuasive techniques by life insurance agents: Prospect Potential Customers to be Persuaded; Message the Customer and Make a Connection; Building Customer Relations; Determine and Understand the Needs of the Customer; Make Use of Social Media to be Known and to Have a Good Standing; Track the Expenses and Make a Financial Health Analysis for the Insurance Coverage; Encourage the Customers through Realization and Other People’s Experiences; Application of Theories and Describing the Purpose of the Policies; Show Consideration and Value to the Customer; Consistent Support and Assistance to the Customers; and Credibility of the Agent. Researchers also found that in customer-agent interactions, highlighting the importance of life insurance was the most effective approach. While one customer was not persuaded, successful persuasive techniques were used with other customers that met their needs.